An overview of forensic medicine specialists, medicolegal services, and the advent of telemedicine in forensics in Nepal - Acharya, Apurba; Bhattarai, Kushal; Aryal, Umesh Raj; Shakya, Arbin; Atreya, Alok; Bista, Binamra (Journal of General Practice and Emergency Medicine of Nepal, 2025)
Forensic medicine in Nepal plays a crucial role in legal and healthcare systems. It involves experts who are integral to the investigation of deaths, analysis of injuries, and cases of sexual abuse, as well as providing expert testimony in legal matters. These professionals determine the cause of death, identify victims in mass disasters, and collaborate with law enforcement to gather evidence, ensuring justice in cases of criminal activities and suspicious deaths. Currently, most of the medicolegal cases are addressed by medical doctors who undergo seventeen days medico-legal training due to lack of forensic medicine specialists, adequate facilities, and modern equipment across Nepal’s provinces. This shortage delays and backlogs case handling, ultimately hindering justice delivery.To address these challenges, the Nepal Medical Council introduced basic guidelines in 2020, advocating for integrating telemedicine in all medical practices including Forensic Medicine, which could significantly enhance service delivery. With at least one forensic medicine expert per province, efforts are being made to improve and standardize medico-legal services. Establishing a standard forensic protocol, including communication methods, specific guidelines, and financial incentives, is essential for shaping the future of forensic medicine experts in Nepal. This approach aims to mitigate the infrastructure inadequacies, ensuring timely intervention, laboratory analysis, and expert opinions, thus improving the overall efficiency and effectiveness of medico-legal services in the country.